The Linkages between Inflation and Inflation Uncertainty in Selected Asian Economies: Evidence from Quantile Regression - JIRANYAKUL, Komain (Journal of Advanced Studies in Finance, 2020)
This paper examines inflation-inflation uncertainty nexus in both inflation targeting and non-inflation targeting economies in Asia. Using monthly data from 1979M1 to 2019M12, the AR(p)-EGARCH model is used to generate inflation uncertainty series. In addition, quantile regression is employed to examine the linkages between inflation and inflation uncertainty in nine Asian countries. The results show that inflation positively causes inflation uncertainty in all economies regardless of whether economies have implemented inflation targeting or not. The Friedman-Ball hypothesis is thus supported. In addition, inflation uncertainty positively causes inflation in most economies. Therefore, the Cukierman-Meltzer hypothesis is likely to be supported. The findings signal the possibility of the real cost of inflation for these economies.